PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN FASILITAS KANTOR TERHADAP KINERJA PEGAWAI DI KANTOR BADAN PENDAPATAN DAERAH KOTA MEDAN - Galuh Rahmi Pertiwi; Erlyanti Erlyanti; Dewi Sundari Tanjung (HIBRUL ULAMA, 2025)
The purpose of this research is to analyze the influence of work motivation, work discipline, and office facilities on employee performance.This research is a quantitative study.The population in this study consists of employees of the Regional Civil Service Agency Office of Medan City.The determination of the research sample uses the saturated sampling technique, meaning the sample is the entire population.The sample in this study consisted of 31 respondents.The data collection instrument used was a questionnaire.The independent variables are work motivation, work discipline, and office facilities, while the dependent variable is employee performance at the Regional Personnel Agency Office of Medan City.The data analysis method used is multiple linear regression.All statements are valid, reliable, and normal.The findings of this research are as follows:The results of the study on work motivation, work discipline, and office facilities simultaneously have a significant effect on employee performance with Fhitung 4.787 > Ftabel 2.96 and a significant probability of 0.008 < 0.05.Therefore, Ho is rejected and Ha is accepted, meaning the hypothesis is accepted.Based on the t-test results on work motivation, a t-value of 2.080 > t-table 1.703 and a significance level of 0.047 < 0.05 were obtained, thus Ho is rejected and Ha is accepted, meaning that work motivation partially has a significant effect on employee performance.The results of the t-test on work discipline obtained a t-value of 1.138 < t-table 1.703 and a significance level of 0.265 > 0.05, therefore Ho is accepted and Ha is rejected, meaning that work discipline does not have a significant partial effect on employee performance.The results of the t-test on office facilities obtained a t-value of 0.478 < t-table 1.703 and a significance level of 0.637 > 0.05, thus Ho is accepted and Ha is rejected, meaning that partially, office facilities do not have a significant effect on employee performance.From the results of this study, it is also known that the coefficient of determination (R square) is 0.347, meaning that 34.7% of employee performance at the Regional Civil Service Agency Office of Medan City is influenced by work motivation, work discipline, and office facilities.Meanwhile, the remaining 65.3% is influenced by other variables that were not examined in this study.